Impact of guidelines implementation on empiric antibiotic treatment for pediatric uncomplicated osteomyelitis and septic arthritis over a ten-year period: Results of the ELECTRIC study (ostEomyeLitis and sEptiC arThritis tReatment in children) - Minotti, Chiara; Tirelli, Francesca; Guariento, Chiara; Sturniolo, Giulia; Giaquinto, Carlo; Da Dalt, Liviana; Zulian, Francesco; Meneghel, Alessandra; Martini, Giorgia; Donà, Daniele (Frontiers in Pediatrics, 2023)
Background Due to the growing evidence of the efficacy of intravenous (IV) cefazolin with an early switch to oral cefalexin in uncomplicated pediatric osteomyelitis (OM) and septic arthritis (SA) in children, we changed our guidelines for empiric antibiotic therapy in these conditions. This study aims at evaluating the impact of the guidelines’ implementation in reducing broad-spectrum antibiotic prescriptions, duration of IV antibiotic treatment and hospital stay, treatment failure and recurrence. Materials and Methods This is a retrospective, observational, quasi-experimental study. The four years pre-intervention were compared to the six years, ten months post-intervention (January 2012, through December 2015; January 2016, through October 31st, 2022). All patients aged 3 months to 18 years with OM or SA were evaluated for inclusion. Each population was divided into three groups: pre-intervention, post-intervention not following the guidelines, and post-intervention following the guidelines. Differences in antibiotic prescriptions such as Days of Therapy (DOT), activity spectrum and Length of Therapy (LOT), length of hospital stay (LOS), broad-spectrum antibiotics duration (bsDOT), treatment failure and relapse at six months were analyzed as outcomes. Results Of 87 included patients, 48 were diagnosed with OM (8 pre-intervention, 9 post-intervention not following the guidelines and 31 post-intervention following the guidelines) and 39 with SA (9 pre-intervention, 12 post-intervention not following the guidelines and 18 post-intervention following the guidelines). In OM patients, IV DOT, DOT/LOT ratio, and bsDOT were significantly lower in the guidelines group, with also the lowest proportion of patients discharged on IV treatment. Notably, significantly fewer cases required surgery in the post-intervention groups. Considering SA, LOS, IV DOT, DOT/LOT ratio, and bsDOT were significantly lower in the guidelines group. The treatment failure rate was comparable among all groups for both OM and SA. There were no relapse cases. The overall adherence was between 72 and 100%. Conclusions The implementation of guidelines was effective in decreasing the extensive use of broad-spectrum antibiotics and combination therapy for both OM and SA. Our results show the applicability, safety, and efficacy of a narrow-spectrum IV empirical antibiotic regimen with cefazolin, followed by oral monotherapy with first/second-generation cephalosporins, which was non-inferior to broad-spectrum regimens.